Correct Answer - Option 5 : Neither Statement I nor Statement II is sufficient to answer the question.

Statement (I):

Let the first even number be 'x'.

And first odd number be 'y'.

So, Even numbers = x, (x + 2), (x + 4)

And odd numbers = y, (y + 2), (y + 4)

∴ The statement I alone is not sufficient to answer the question

Statement (II):

According to the question,

(y + 2) - (x + 2) = 7

⇒ y - x = 7

∴ Statement II alone is not sufficient.

**∴ Neither Statement I nor Statement II is sufficient to answer the question.**